Yeast Systems Biology: Model Organism and Cell Factory. Issue 9 (20th May 2019) - Nielsen, Jens
Abstract : For thousands of years, the yeast Saccharomyces cerevisiae ( S. cerevisiae ) has served as a cell factory for the production of bread, beer, and wine. In more recent years, this yeast has also served as a cell factory for producing many different fuels, chemicals, food ingredients, and pharmaceuticals. S. cerevisiae, however, has also served as a very important model organism for studying eukaryal biology, and even today many new discoveries, important for the treatment of human diseases, are made using this yeast as a model organism. Here a brief review of the use of S. cerevisiae as a model organism for studying eukaryal biology, its use as a cell factory, and how advances in systems biology underpin developments in both these areas, is provided. Abstract : Through engineering yeast metabolism it is possible to produce many different molecules finding applications as biofuels, chemicals, and pharmaceuticals. Relying on the extensive knowledge base of yeast, due to its many years of use as a model organism, has assisted in improving new design strategies, and also the advancement in systems biology has enabled the improved design of efficient cell factories.